2008
DOI: 10.1080/00140130802238630
|View full text |Cite
|
Sign up to set email alerts
|

The role of contextual factors for musculoskeletal disorders in the New Zealand meat processing industry

Abstract: Musculoskeletal disorders (MSD) are the leading cause of occupational injury internationally. In New Zealand, the highest incidence of MSD is in meat processing, accounting for over half the injury compensation costs for the sector. MSD in meat processing have proven highly resistant to physical, micro-level interventions, suggesting a new approach is required. This paper reports on part of a 2-year study looking at MSD in the New Zealand meat processing industry. The qualitative study involved interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…While risk factors from all three groups can be considered as independent predictors of MSD, it is now well accepted that it is a combination of risk factors that result in MSD rather than one element of risk (Bongers, Ijmker, van den Heuvel, Blatter, 2006;Da Costa and Vieira, 2010;Hauke et al, 2011;NRC-IOM, 2001;Silverstein and Clark, 2004). Causation models continue to develop from industry-based research that also highlight some of the broader interactions that can occur in occupational settings, creating conditions under which MSD may be more likely to occur (for example, Faucett, 2005;Karsh, 2006;Lee et al, 2010;NRC-IOM, 2001;Tappin et al, 2008). Examples of such conditions might include supply chain influences on work scheduling and task exposure, and impacts of remunerations systems on workload, work pace and work hours.…”
Section: Linking Safety Culture To Msdmentioning
confidence: 97%
See 1 more Smart Citation
“…While risk factors from all three groups can be considered as independent predictors of MSD, it is now well accepted that it is a combination of risk factors that result in MSD rather than one element of risk (Bongers, Ijmker, van den Heuvel, Blatter, 2006;Da Costa and Vieira, 2010;Hauke et al, 2011;NRC-IOM, 2001;Silverstein and Clark, 2004). Causation models continue to develop from industry-based research that also highlight some of the broader interactions that can occur in occupational settings, creating conditions under which MSD may be more likely to occur (for example, Faucett, 2005;Karsh, 2006;Lee et al, 2010;NRC-IOM, 2001;Tappin et al, 2008). Examples of such conditions might include supply chain influences on work scheduling and task exposure, and impacts of remunerations systems on workload, work pace and work hours.…”
Section: Linking Safety Culture To Msdmentioning
confidence: 97%
“…Over the past two decades, work-related MSD research has increasingly focused on three groups of risk factors e individual, psychosocial, and physical, as well as interactions between them, in seeking to explain the continued high reported incidence of MSD in many industry sectors internationally (Bernard, 1997;NRC-IOM, 2001;Tappin et al, 2008). While risk factors from all three groups can be considered as independent predictors of MSD, it is now well accepted that it is a combination of risk factors that result in MSD rather than one element of risk (Bongers, Ijmker, van den Heuvel, Blatter, 2006;Da Costa and Vieira, 2010;Hauke et al, 2011;NRC-IOM, 2001;Silverstein and Clark, 2004).…”
Section: Linking Safety Culture To Msdmentioning
confidence: 99%
“…This however was simply ergonomics in action (Wilson, 2005) and is not described as participative. Further details on these two earlier stages of the study are reported in Tappin et al (2008aTappin et al ( , 2008b. A participative approach was adopted for the final stage of the study; the development of interventions for the industry.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of information limits the planning and implementation of policies for the prevention of work accidents. Official data on occupational accidents do not accurately show the results of accidents and mishaps if a CAT is not issued (Kearney, 2010;Tappin et al, 2008;Reardon & Farina, 2010;Stearns et al, 1999).…”
Section: Introductionmentioning
confidence: 99%